(p-7)*p-1=

Simple and best practice solution for (p-7)*p-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (p-7)*p-1= equation:


Simplifying
(p + -7) * p + -1 = 0

Reorder the terms:
(-7 + p) * p + -1 = 0

Reorder the terms for easier multiplication:
p(-7 + p) + -1 = 0
(-7 * p + p * p) + -1 = 0
(-7p + p2) + -1 = 0

Reorder the terms:
-1 + -7p + p2 = 0

Solving
-1 + -7p + p2 = 0

Solving for variable 'p'.

Begin completing the square.

Move the constant term to the right:

Add '1' to each side of the equation.
-1 + -7p + 1 + p2 = 0 + 1

Reorder the terms:
-1 + 1 + -7p + p2 = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -7p + p2 = 0 + 1
-7p + p2 = 0 + 1

Combine like terms: 0 + 1 = 1
-7p + p2 = 1

The p term is -7p.  Take half its coefficient (-3.5).
Square it (12.25) and add it to both sides.

Add '12.25' to each side of the equation.
-7p + 12.25 + p2 = 1 + 12.25

Reorder the terms:
12.25 + -7p + p2 = 1 + 12.25

Combine like terms: 1 + 12.25 = 13.25
12.25 + -7p + p2 = 13.25

Factor a perfect square on the left side:
(p + -3.5)(p + -3.5) = 13.25

Calculate the square root of the right side: 3.640054945

Break this problem into two subproblems by setting 
(p + -3.5) equal to 3.640054945 and -3.640054945.

Subproblem 1

p + -3.5 = 3.640054945 Simplifying p + -3.5 = 3.640054945 Reorder the terms: -3.5 + p = 3.640054945 Solving -3.5 + p = 3.640054945 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + p = 3.640054945 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + p = 3.640054945 + 3.5 p = 3.640054945 + 3.5 Combine like terms: 3.640054945 + 3.5 = 7.140054945 p = 7.140054945 Simplifying p = 7.140054945

Subproblem 2

p + -3.5 = -3.640054945 Simplifying p + -3.5 = -3.640054945 Reorder the terms: -3.5 + p = -3.640054945 Solving -3.5 + p = -3.640054945 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + p = -3.640054945 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + p = -3.640054945 + 3.5 p = -3.640054945 + 3.5 Combine like terms: -3.640054945 + 3.5 = -0.140054945 p = -0.140054945 Simplifying p = -0.140054945

Solution

The solution to the problem is based on the solutions from the subproblems. p = {7.140054945, -0.140054945}

See similar equations:

| 3n+5=5n-5 | | 4v*a=8w | | 3(x-5)/2=2(x+10)/3 | | 8p-7q=-19 | | 4sinx-8=0 | | 3p-2q=-9 | | 3w^2-4w=84 | | 10x+5y-5=170 | | 7m+11=-88 | | 6n+11=27 | | p+1(p+3)(p+7)= | | 2m+11=-88 | | .625x=20 | | -7+2(x-3)= | | .17x=3 | | 0=0.25x+1 | | log(x^2+4)-log(x+2)=2+log(x-2) | | .7(x)=58 | | .7(x)=41 | | .7(x)=31 | | .7(x)=11.07 | | .7(x)=6.16 | | .7(x)=7.16 | | .7(x)=8.10 | | -3v=195 | | (5n+2)(3n-7)=0 | | (9-x)(2x^2-4)(9x^3+6x-27)(5x-2)=0 | | .7(x)=7.50 | | 3x^3+2x^2+4=28 | | .7(x)=3.90 | | 7(x)=3.90 | | .7(x)=6 |

Equations solver categories